Discovery and Total Synthesis of Natural Cystobactamid Derivatives with Superior Activity against Gram‐Negative Pathogens. Issue 41 (29th August 2017) - Hüttel, Stephan; Testolin, Giambattista; Herrmann, Jennifer; Planke, Therese; Gille, Franziska; Moreno, Maria; Stadler, Marc; Brönstrup, Mark; Kirschning, Andreas; Müller, Rolf
Abstract: Antibiotic discovery and development is challenging as chemical scaffolds of synthetic origin often lack the required pharmaceutical properties, and the discovery of novel ones from natural sources is tedious. Herein, we report the discovery of new cystobactamids with a significantly improved antibacterial profile in a detailed screening of myxobacterial producer strains. Some of these new derivatives display antibacterial activities in the low‐μg mL −1 range against Gram‐negative pathogens, including clinical isolates of Klebsiella oxytoca, Pseudomonas aeruginosa, and fluoroquinolone‐resistant Enterobacteriaceae, which were not observed for previously reported cystobactamids. Our findings provide structure–activity relationships and show how pathogen resistance can be overcome by natural scaffold diversity. The most promising derivative 861‐2 was prepared by total synthesis, enabling further chemical optimization of this privileged scaffold. Abstract : From nature's toolbox : A concise study with myxobacterial producer strains yielded novel cystobactamid derivatives that display superior activity against Gram‐negative pathogens. The most promising derivative was obtained by total synthesis, and will serve as a starting point for the further optimization of these gyrase inhibitors and their development as antibacterial drugs. SAR=structure–activity relationship.